Did the Bundesbank Target Monetary Expansion or Inflation? Evidence from Monetary Base Growth - Galina Boeva; Roland Vaubel (Swiss Journal of Economics and Statistics, 2012)
Several empirical studies have suggested that the Bundesbank has pursued inflation targets rather than monetary targets. We find that, in the period from 1979 III to 1998 IV, changes in adjusted monetary base growth reacted negatively and significantly to deviations from target monetary expansion as measured relative to the nearest margin of the target band if, and only if, no control variables are added. By contrast, deviations of the inflation rate from the inflation objective used to derive the money supply target never had any significant effect on changes in adjusted monetary base growth.
Keywords: E52; E58; E42; 330; Deutsche Bundesbank; monetary policy; money supply targets; inflation targets